Architectural analysis of Lima’s pulperías from colonial times to the present in the traditions «El pleito de los pulperos» («The fight of the pulperos») and «La calle de la Manita» («The street of the Manita») - Pajuelo Salazar, Abigail Yamile (2023)
In this article, we will analyze the evolution of the pulperías as multifunctional spaces in the mercantile and social aspect of Lima’s colonial architecture, which would be the beginning of what we know today as commercial centers. In order to highlight and compare their main characteristics that prevail until today, we will establish the Plaza San Miguel and Jockey Plaza shopping malls as objects of study. The research is oriented to the main influence of the architectural design to cover the user’s needs, based on the stories «El pleito de los pulperos» and «La calle de la Manita» by the writer Ricardo Palma.